Single-Dose Lentiviral Mediated Gene Therapy Recovers CFTR Function in Cystic Fibrosis Knockout Rats - Reyne, Nicole; Cmielewski, Patricia; McCarron, Alexandra; Delhove, Juliette; Parsons, David; Donnelley, Martin (Frontiers in Pharmacology, 2021)
Cystic fibrosis (CF) is a genetic disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene, resulting in defective ion transport in the airways. Addition of a functioning CFTR gene into affected airway cells has the potential to be an effective treatment for lung disease. The therapeutic efficacy of airway gene transfer can be quantified in animal models by assessing ion transport in the treated nasal epithelium using the nasal potential difference (PD) measurement technique. The nasal PD technique is routinely used in CF mice, however when applied to a recently developed CF rat model those animals did not tolerate the initial nasal PD assessment, therefore the procedure was firstly optimised in rats. This study evaluated the effect of lentiviral (LV)-mediated CFTR airway gene delivery on nasal PD in a CFTR knockout rat model. LV gene vector containing the CFTR gene tagged with a V5 epitope tag (LV-V5-CFTR) was delivered to the nasal epithelium of CF rats, and one week later nasal PD was analysed. This study demonstrated for the first time that LV-V5-CFTR treatment produced a mean correction of 46% towards wild-type chloride response in treated CF rats. Transduced cells were subsequently identifiable using V5 immunohistochemical staining. These findings in the nose validate the use of airway gene therapy for future lung based experiments.